Analisis Penguasaan Siswa Sekolah Menengah Atas pada Materi Geometri - Roskawati Roskawati; M. Ikhsan; Dadang Juandi (Universitas Syiah Kuala, 2015)
Geometry is one of the subjects studied at the high school level. Learning geometry includes the position, distance, and angle of the elements of a space. This study was a qualitative study aimed to look at the students' mastery of geometry. Subjects in this study were students in high schools in Banda Aceh were categorized in high school, medium, and low. Categories of student mastery of the geometry were analyzed based on mistakes made by students in answering the questions. Based on the data analysis it can be concluded that (i) high school students in Banda Aceh had not mastered geometry, (ii) there were mistakes made by students in answering the question of geometry. Mistakes made by students include misconceptions, operation, and analysis, (iii) the student mistakes caused by (1) not mastered the concepts, (2) inability to perform the operation, and (3) not able to perform the analysis in accordance with the expected completion problem. Important information obtained through this study was that the mistakes made by students in solving geometry had a close connection with the student's mastery of geometry.